Percutaneous Endoscopic Backhand Holding (EBH) Technique for Extraforaminal Lumbar Disc Herniations: A Modified Operative Technique - Kong M; Gao C; Hao M; Ma X; Zhao J; Luan J; Lin Y; Jin C; Li Q (Journal of Pain Research)
Meng Kong,1 Changtong Gao,2 Meng Hao,1 Xuexiao Ma,3 Jindong Zhao,1 Jian Luan,1 Yong Lin,1 Canghai Jin,1 Qiang Li1 1Department of Spine Surgery, Qingdao Municipal Hospital, Qingdao, Shandong, People’s Republic of China; 2Department of Oncology, Qingdao Municipal Hospital, Qingdao, Shandong, People’s Republic of China; 3Department of Spine Surgery, Affiliated Hospital of Qingdao University, Qingdao, Shandong, People’s Republic of ChinaCorrespondence: Qiang Li, Department of Spine Surgery, Qingdao Municipal Hospital, No. 5, Middle Dong Hai Road, Qingdao, Shandong Province, 266071, People’s Republic of China, Tel +8617669757975, Email qdslliqiang@163.com Canghai Jin, Department of Spine Surgery, Qingdao Municipal Hospital, No. 5, Middle Dong Hai Road, Qingdao, Shandong Province, 266071, People’s Republic of China, Tel +8618306483878, Email jincanghai@126.comBackground: Percutaneous endoscopic lumbar discectomy (PELD) is a minimally invasive surgical (MIS) procedure rapidly improved in the surgical treatment of lumbar disc herniation (LDH). For the treatment of extraforaminal lumbar disc herniations (ELDH), microendoscopic discectomy (MED) or traditional Transforaminal Lumbar Interbody Fusion (MIS-TLIF) are commonly used, but limitations exist due to bony resection. Many classic surgical approaches for PELD have inherent disadvantage when removing migrated ELDH.Objective: We aimed to present the results of a series of PELD cases that were operated using a modified endoscopic backhand holding (EBH) approach for the treatment of ELDH.Methods: Seventy-two patients diagnosed with ELDH who underwent PELD via the EBH approach from January 2018 to December 2022 were retrospectively assessed. Pre- and postoperative clinical data, radiographic findings, and surgical techniques were investigated. Neurological recovery examinations were performed preoperatively and at 3 days, 1 month, 3 months, 6 months, 1 year postoperatively.Results: No major intraoperative complications were noted. Significant improvement in back and leg pain was observed in visual analogue scale (VAS) score, and the mean ODI was decreased from preoperative 78% (range = 60– 98%) to postoperative 30% (20– 40%) (P < 0.001) at 1-month follow-up and obtained further improvement at 1 year (mean ODI = 11%; range = 2– 20%). All patients showed progressive improvement in their initial neurological deficits, with complete recovery of motor weakness. According to the Macnab criteria, overall excellent and good outcomes were obtained in 67 patients (95.7%) – 57 excellent (81.4%), and 10 (14.3%) good – with fair outcomes in three patients (4.3%) at the time of last follow-up.Conclusion: Percutaneous endoscopic backhand holding is a minimally invasive, safe, valuable, and efficacious surgical procedure for treating ELDH. It is important that surgeons perform PELD using the technique they know best to ensure successful implementation of the surgery.Keywords: endoscopic backhand holding, PELD, extraforaminal lumbar disc herniations, modified technique, minimally invasive surgical procedure